2018
DOI: 10.1111/jicd.12369
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of periostin, sclerostin, receptor activator of nuclear factor‐κB, and receptor activator of nuclear factor‐κB ligand genes in severe chronic periodontitis

Abstract: Aim The aim of the present study was to determine and compare the expression profile of periostin (POSTN), sclerostin (SOST), receptor activator nuclear factor‐κB (RANK), and RANK ligand (RANKL) genes in gingival tissue samples collected from healthy gingiva (control) and severe chronic periodontitis sites. Methods Fifty systemically‐healthy individuals was enrolled in the present case‐control study. Gingival tissue samples were obtained from healthy gingiva (N = 25) and sites with severe chronic periodontitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…A study of periodontal disease tissue specimens found that the mRNA expression of RANKL was upregulated in periodontal disease tissues, while the mRNA expression of OPG was weakened 105 . It has been reported that there is a strong positive correlation between the relative ratio of RANKL/OPG and the severity of periodontal disease 106 . These data indicate that local RANKL/OPG levels are related to periodontal absorption.…”
Section: Th17/treg Imbalance and Periodontal Bone Resorptionmentioning
confidence: 94%
“…A study of periodontal disease tissue specimens found that the mRNA expression of RANKL was upregulated in periodontal disease tissues, while the mRNA expression of OPG was weakened 105 . It has been reported that there is a strong positive correlation between the relative ratio of RANKL/OPG and the severity of periodontal disease 106 . These data indicate that local RANKL/OPG levels are related to periodontal absorption.…”
Section: Th17/treg Imbalance and Periodontal Bone Resorptionmentioning
confidence: 94%
“…Five studies were conducted in China, 46,52,54,59,60 3 in the USA, 50,51,55 2 in India, 48,58 2 in Turkey, 45,47 and the others were from Brazil, 57 Chile, 49 Thailand, 56 and Iran 53 . The majority of the studies were case–control studies ( n = 12), 45,50–60 while randomized clinical trials and non‐randomized clinical interventional studies were also included. The total number of periodontitis patients in the test groups ranged from 11 to 44 (periodontitis group), whereas the control group included 5 to 29 periodontally healthy individuals (healthy group).…”
Section: Resultsmentioning
confidence: 99%
“…Periodontitis and health definitions were quite heterogeneous across the included studies utilizing various cutoffs in periodontal parameters. Eight studies examined GCF samples only, 45–51,53 two studies included both GCF and gingival tissue samples, 59,60 and one study sampled gingival tissue and serum, 57 whereas the remaining five studies included gingival tissue only 52,54–56,58 . In 10 publications, 45–49,53,56,58–60 the authors investigated the levels of only one Wnt signaling agonist or antagonist, while the remaining six included at least two 50–52,54,55,57 .…”
Section: Resultsmentioning
confidence: 99%
“…In clinical studies investigating periostin levels in the gingival crevicular fluid (GCF) [ 75 , 76 ] and Pstn mRNA in tissues [ 77 ] at different stages of periodontal disease, it was shown that the total amount and concentration of periostin in the GCF, as well as Postn mRNA levels, are reduced with the progression and severity of the disease from healthy controls to chronic periodontitis groups and correlate negatively with clinical parameters of disease [ 77 ]. When looking at the expression profile of periostin in GCF/wound fluid over time after periodontal surgery, it was shown that periostin levels increase after surgery, peak at 48 h and are higher in patients with the periodontal disease when compared to healthy controls.…”
Section: Gla-containing Ecm Proteinsmentioning
confidence: 99%